Religious Moderation in the Presiden Joko Widodo Administration: Tools for Religious Harmony or Politics? - Izzul Fatchu Reza (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
Religious moderation has always been promoted and socialized by the government to all elements of society, especially by the Ministry of Religious Affairs of the Republic of Indonesia since 2016. However, repression continues against a certain religion and group. This article discusses whether religious moderation is successful or not as an effective tool for strengthening interreligious tolerance and confusion in order to create a just and peaceful state in the era of the Joko Widodo administration. The research used content analysis methods from eleven online news media outlets with a historical case study approach. The results showed that the religious moderation under President Joko Widodo is contrary to the spirit of tolerance and anti-violence, which is the main principle of moderation. There is a considerable amount of persecution, violence, and disobedience directed towards individuals or groups that associate with Islamists or apply Islamic rules to themselves or their groups due to the top-down approach of implementation design, lack of human resources, and lack of monitoring of religious moderation indicators. Furthermore, there is a call for religious moderation to be exercised in a more balanced and impartial manner towards certain groups while at the same time being more restrictive towards certain other groups.